KUALITAS BUTIR SOAL UJIAN AKHIR MADRASAH IBTIDAIYAH GUGUS II TAHUN PELAJARAN 2010/2011 DI KOTA PALANGKA RAYA - supriadi, Gito (Jurnal Studi Agama dan Masyarakat, 2013)
The objectives of this study were to analyze and describe the difficulty level, the item discrimination, the validity, and the reliability of the test items in Madrasah Ibtidaiyah City Cluster II on subjects of Quran Hadith, Morals Aqeedah, Fiqh, Arabic, and SKI in Academic Year of 2010/2011 in Palangka Raya.This study used descriptive quantitative approach. The technique that was used for data collection was documentation technique in the form of exam questions and studentsâ answer sheets. Meanwhile the technique for data analysis used statistical analysis that consisted of formulas of difficulty level item, item discrimination, validity, and reliability of the test items.The results of the study showed that: (1) the difficulty level on Quran Hadith test items was eligible which there were 6 items found, Morals Aqeedah test items had no difficulty level that met the criteria of good items, as for Fiqh test items, there were 6 items that included criteria for difficulty level of good items, and the last were Arabic test items that had 17 good items which met the criteria. (2) The item discrimination that met the criteria for Quran Hadith were 11 items, Morals Aqeedah were 3 items, Fiqh were not found, Arabic and SKI were only 1 item found. (3) From 50 test items, most of the items on the 5 subjects met the criteria of validity as Quran Hadith had 47 valid items, Morals Aqeedah had 29, Fiqh had 46, Arabic had 47, and SKI had 45. (4) Correlation index for reliability showed that Quran Hadith, Fiqh, Arabic, and SKI included in reliable category, whereas only Morals Aqeedah did not